2020
DOI: 10.1093/ehjacc/zuaa020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of patients with prior coronary artery bypass grafting and suspected acute myocardial infarction

Abstract: Aims Diagnosis of acute myocardial infarction (AMI) can be challenging in patients with prior coronary artery bypass grafting (CABG). Methods and results Final diagnoses were adjudicated by two independent cardiologists using the universal definition of AMI among patients presenting to the emergency department (ED) with suspected AMI. Diagnostic accuracy of 34 chest pain characteristics (CPCs) and four electrocardiogram (ECG)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This was a secondary analysis from the APACE (Advantageous Predictors of Acute Coronary Syndromes Evaluation) study. APACE is a multicenter, international, prospective diagnostic study ( NCT00470587 ), 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 conducted in 12 EDs in 5 different European countries, enrolling patients >18 years of age presenting to EDs with nontraumatic acute chest pain as the main symptom. Patients were excluded if they had had prehospital cardiopulmonary resuscitation, were in shock, or had terminal kidney failure on long-term hemodialysis.…”
Section: Methodsmentioning
confidence: 99%
“…This was a secondary analysis from the APACE (Advantageous Predictors of Acute Coronary Syndromes Evaluation) study. APACE is a multicenter, international, prospective diagnostic study ( NCT00470587 ), 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 conducted in 12 EDs in 5 different European countries, enrolling patients >18 years of age presenting to EDs with nontraumatic acute chest pain as the main symptom. Patients were excluded if they had had prehospital cardiopulmonary resuscitation, were in shock, or had terminal kidney failure on long-term hemodialysis.…”
Section: Methodsmentioning
confidence: 99%
“…The need for more extensive diagnostic work-up often including cardiac imaging in patients with prior CABG is further emphasized by the high prevalence of MI observed in this vulnerable patient subgroup. [2] Given the difficulty of angiographically identifying the culprit lesion in patients with prior CABG, sophisticated non-invasive imaging using e.g. PET-scanning may by warranted in many patients remaining in the observe-zone.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In patients with prior coronary artery bypass grafting (CABG) presenting with acute chest pain, the prevalence of acute myocardial infarction (MI) was two-fold higher and that of unstable angina three-fold higher compared to patients without prior CABG. [2] Therefore, it is of major concern that recent pilot studies have suggested that all three pillars of the early diagnosis of MI, chest pain characteristics, 12-lead ECG, and high-sensitivity cardiac troponin T (hs-cTnT) may have lower diagnostic accuracy in patients with prior CABG. [2], [3] While clinical practice and clinical practice guidelines in general assume that the release of cTnI and cTnT into the circulation reflects identical pathophysiological processes,important pathophysiological differences between cTnT and cTnI, including circadian rhythm of cTnT, but not cTnI, and stronger influence of skeletal muscle disease and renal dysfunction on cTnT, as well as possible differences among different hs-cTnI assays, have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations